Effect of Solution pH on the Photo-Oxidation of 4-Chlorophenol by Synthesized Silver-Zinc Oxide Photocatalyst - Nur Syafiqa Hazirah Razali; Hayati Mohamad Mukhair; Kian Mun Lee; Mohd Izham Saiman; Abdul Halim Abdullah (Universitas Gadjah Mada, 2022)
Due to its toxicity, 4-chlorophenol (4CP) must be removed from the wastewater before discharging into open water. In this work, ZnO and Ag-ZnO photocatalysts were prepared via a solvothermal method under mild conditions (150 °C), followed by calcination at 300 °C and then characterized. The addition of Ag resulted in a change of the ZnO morphologies, which exhibited wurtzite structure, from irregular to rod-like shape, lower bandgap energy, and a lower electron-hole recombination rate. The 0.6 Ag-ZnO catalyst showed the highest efficiency in the photooxidation of 4CP under UV irradiation. Molecular 4CP exists in acidic and near-neutral conditions (pH 4 and 6) and is stable towards UV irradiation. Photooxidation of 2.3 × 10–4 mol/L 4CP by 0.8 g of 0.6% Ag-ZnO resulted in 67% removal of molecular 4CP at pH 6 with a rate constant of 4.0 × 10–3 min–1. Under similar conditions, a complete photooxidation of the anionic 4CP was observed at pH 11 with a rate constant of 1.4 × 10–2 min–1. The holes and superoxide radicals are the species responsible for molecular 4CP photoooxidation, while hydroxyl radicals are the dominant species for anionic 4CP. The prepared Ag/ZnO photocatalyst exhibit good potential to efficiently oxidize 4CP in both acidic and alkaline conditions.